PMP (R) in Depth : project management professional certification study guide for the PMP (r) exam - Sanghera, Paul (APRESS, 2019)
Use this study guide to prepare for the Project Management Professional (PMP) exam administered by the Project Management Institute (PMI). The revised third edition of the best-selling PMP in Depth, updated to the sixth edition of PMBOK, has a laser-sharp focus on the exam objectives for project managers and others who want to pass the PMP exam. No prior knowledge of project management is assumed. The chapters and the sections within each chapter are presented in a logical learning sequence. The concepts and topics, both simple and complex, are clearly explained when they appear for the first time. This facilitates step-wise learning, prevents confusion, and makes this book useful for those who want to get up to speed quickly to pass the PMP exam, even if you are new to the discipline of project management. This book tells the story of project management in a cohesive, concise, yet comprehensive fashion. Unlike most PMP exam books, PMP in Depth covers the material in the order in which projects are actually run in the real world. The book is an easy-to-understand guide that is valuable both before and after the exam. What You'll Learn: Understand the body of knowledge required to earn the Project Management Professional (PMP) certification Acquire the knowledge needed to enter the field of project management and successfully manage projects in any field.